Investigating the Export Procedure Awareness of the Residents of Laligurans Municipality - Rai, Arjun (Dristikon: A Multidisciplinary Journal, 2021)
This survey examined the association between the gender of the respondents and their desire to join or form a local cooperative association, perception towards the quality of locally grown agricultural products, and practice of selling locally produced agricultural products of the residents of Musunkhel, ward number 3 of Laligurans Municipality of Tehrathum district, Province No.1, Nepal. The population in the study comprised all the households of ward number 3 of Laligurans Municipality. This survey used a standardized questionnaire to collect primary data from 92 households from the targeted area. However, this study included 79 households only. The remaining households were filtered during the data curation and cleaning process. The collected data were processed in the Statistical Package for the Social Science (SPSS), version 25. Data were analyzed using descriptive and inferential statistical tools. The study's findings indicated an insignificant association between gender and desire to join or form a local cooperative association, perception towards the quality of locally grown agricultural products, and practice of selling locally produced agricultural products. The study also found that the level of qualification does not influence awareness of the export process. However, relatively respondents with lower academic qualifications were aware of the export procedure.